If a directrix of a hyperbola centered at the origin passing through the point $\left( 4,-2\sqrt{3} \right)$ is $5x=4\sqrt{5}$ and its eccentricity is e, then:
(a) $4{{e}^{4}}-24{{e}^{2}}+35=0$,
(b) $4{{e}^{4}}+8{{e}^{2}}-35=0$,
(c) $4{{e}^{4}}-12{{e}^{2}}-27=0$,
(d) $4{{e}^{4}}-24{{e}^{2}}-27=0$.
Answer
Verified
472.5k+ views
Hint: We start solving the problem by recalling the definitions of hyperbola, eccentricity and directrix with center at origin. We compare the standard form of directrix and the equation of given directrix to get the value of a in terms of eccentricity. We then use eccentricity to find the value of b in terms of eccentricity. We then substitute the obtained values of a, b and the given point in the equation of hyperbola and make necessary calculations to get the required result.
Complete step-by-step answer:
According to the problem, we have a hyperbola centered at origin and passing through the point $\left( 4,-2\sqrt{3} \right)$. The equation of directrix of this hyperbola is $5x=4\sqrt{5}$ and eccentricity is e.
Let us draw all the given information.
We know that the equation of the hyperbola centered at origin is $\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$ and we know that the eccentricity of the hyperbola is $e=\dfrac{\sqrt{{{a}^{2}}+{{b}^{2}}}}{a}$ ---(1).
We know that equation of one of the directrix of the hyperbola is given as $x=\dfrac{a}{e}$ ---(2).
According to the problem, we have the equation of directrix of this hyperbola is $5x=4\sqrt{5}$.
$\Rightarrow x=\dfrac{4\sqrt{5}}{5}$.
$\Rightarrow x=\dfrac{4}{\sqrt{5}}$ ---(3).
Comparing equations (2) and (3), we get $\dfrac{a}{e}=\dfrac{4}{\sqrt{5}}$.
$a=\dfrac{4e}{\sqrt{5}}$.
${{a}^{2}}=\dfrac{16{{e}^{2}}}{5}$ ---(4).
From equation (1), we have $e=\dfrac{\sqrt{{{a}^{2}}+{{b}^{2}}}}{a}$.
$\Rightarrow {{e}^{2}}=\dfrac{{{a}^{2}}+{{b}^{2}}}{{{a}^{2}}}$.
$\Rightarrow {{a}^{2}}{{e}^{2}}={{a}^{2}}+{{b}^{2}}$.
$\Rightarrow {{a}^{2}}{{e}^{2}}-{{a}^{2}}={{b}^{2}}$.
$\Rightarrow {{a}^{2}}\left( {{e}^{2}}-1 \right)={{b}^{2}}$.
From equation (4),
$\Rightarrow \dfrac{16{{e}^{2}}\left( {{e}^{2}}-1 \right)}{5}={{b}^{2}}$ ---(5).
We substitute equations (4) and (5) in the equation of hyperbola $\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$.
$\Rightarrow \dfrac{{{x}^{2}}}{\dfrac{16{{e}^{2}}}{5}}-\dfrac{{{y}^{2}}}{\dfrac{16{{e}^{2}}\left( {{e}^{2}}-1 \right)}{5}}=1$.
$\Rightarrow \dfrac{{{x}^{2}}}{1}-\dfrac{{{y}^{2}}}{\left( {{e}^{2}}-1 \right)}=\dfrac{16{{e}^{2}}}{5}$ ---(6).
We substitute the point $\left( 4,-2\sqrt{3} \right)$ in equation (6), as the equation of hyperbola passes through it.
$\Rightarrow \dfrac{{{\left( 4 \right)}^{2}}}{1}-\dfrac{{{\left( -2\sqrt{3} \right)}^{2}}}{\left( {{e}^{2}}-1 \right)}=\dfrac{16{{e}^{2}}}{5}$.
$\Rightarrow 16-\dfrac{12}{\left( {{e}^{2}}-1 \right)}=\dfrac{16{{e}^{2}}}{5}$.
\[\Rightarrow \dfrac{4\left( {{e}^{2}}-1 \right)-3}{\left( {{e}^{2}}-1 \right)}=\dfrac{4{{e}^{2}}}{5}\]
\[\Rightarrow 5\times \left( 4{{e}^{2}}-4-3 \right)=4{{e}^{2}}\times \left( {{e}^{2}}-1 \right)\].
\[\Rightarrow 5\times \left( 4{{e}^{2}}-7 \right)=4{{e}^{2}}\times \left( {{e}^{2}}-1 \right)\].
\[\Rightarrow 20{{e}^{2}}-35=4{{e}^{4}}-4{{e}^{2}}\].
\[\Rightarrow 4{{e}^{4}}-4{{e}^{2}}-20{{e}^{2}}+35=0\].
\[\Rightarrow 4{{e}^{4}}-24{{e}^{2}}+35=0\].
We have found the condition for eccentricity of hyperbola as \[4{{e}^{4}}-24{{e}^{2}}+35=0\].
∴ The condition for eccentricity of hyperbola is \[4{{e}^{4}}-24{{e}^{2}}+35=0\].
So, the correct answer is “Option A”.
Note: We can also solve the problem by finding the value of eccentricity using the value of $\dfrac{a}{e}$ and substituting it in the options to verify which is the correct option. We need to make sure about the center of the given hyperbola. If the center changes, then the total answer changes with a lot of deviation from the answer we just had. Similarly, we expect to find the values of a, b and also the equation of the axes, foci of the given hyperbola.
Complete step-by-step answer:
According to the problem, we have a hyperbola centered at origin and passing through the point $\left( 4,-2\sqrt{3} \right)$. The equation of directrix of this hyperbola is $5x=4\sqrt{5}$ and eccentricity is e.
Let us draw all the given information.
We know that the equation of the hyperbola centered at origin is $\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$ and we know that the eccentricity of the hyperbola is $e=\dfrac{\sqrt{{{a}^{2}}+{{b}^{2}}}}{a}$ ---(1).
We know that equation of one of the directrix of the hyperbola is given as $x=\dfrac{a}{e}$ ---(2).
According to the problem, we have the equation of directrix of this hyperbola is $5x=4\sqrt{5}$.
$\Rightarrow x=\dfrac{4\sqrt{5}}{5}$.
$\Rightarrow x=\dfrac{4}{\sqrt{5}}$ ---(3).
Comparing equations (2) and (3), we get $\dfrac{a}{e}=\dfrac{4}{\sqrt{5}}$.
$a=\dfrac{4e}{\sqrt{5}}$.
${{a}^{2}}=\dfrac{16{{e}^{2}}}{5}$ ---(4).
From equation (1), we have $e=\dfrac{\sqrt{{{a}^{2}}+{{b}^{2}}}}{a}$.
$\Rightarrow {{e}^{2}}=\dfrac{{{a}^{2}}+{{b}^{2}}}{{{a}^{2}}}$.
$\Rightarrow {{a}^{2}}{{e}^{2}}={{a}^{2}}+{{b}^{2}}$.
$\Rightarrow {{a}^{2}}{{e}^{2}}-{{a}^{2}}={{b}^{2}}$.
$\Rightarrow {{a}^{2}}\left( {{e}^{2}}-1 \right)={{b}^{2}}$.
From equation (4),
$\Rightarrow \dfrac{16{{e}^{2}}\left( {{e}^{2}}-1 \right)}{5}={{b}^{2}}$ ---(5).
We substitute equations (4) and (5) in the equation of hyperbola $\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{b}^{2}}}=1$.
$\Rightarrow \dfrac{{{x}^{2}}}{\dfrac{16{{e}^{2}}}{5}}-\dfrac{{{y}^{2}}}{\dfrac{16{{e}^{2}}\left( {{e}^{2}}-1 \right)}{5}}=1$.
$\Rightarrow \dfrac{{{x}^{2}}}{1}-\dfrac{{{y}^{2}}}{\left( {{e}^{2}}-1 \right)}=\dfrac{16{{e}^{2}}}{5}$ ---(6).
We substitute the point $\left( 4,-2\sqrt{3} \right)$ in equation (6), as the equation of hyperbola passes through it.
$\Rightarrow \dfrac{{{\left( 4 \right)}^{2}}}{1}-\dfrac{{{\left( -2\sqrt{3} \right)}^{2}}}{\left( {{e}^{2}}-1 \right)}=\dfrac{16{{e}^{2}}}{5}$.
$\Rightarrow 16-\dfrac{12}{\left( {{e}^{2}}-1 \right)}=\dfrac{16{{e}^{2}}}{5}$.
\[\Rightarrow \dfrac{4\left( {{e}^{2}}-1 \right)-3}{\left( {{e}^{2}}-1 \right)}=\dfrac{4{{e}^{2}}}{5}\]
\[\Rightarrow 5\times \left( 4{{e}^{2}}-4-3 \right)=4{{e}^{2}}\times \left( {{e}^{2}}-1 \right)\].
\[\Rightarrow 5\times \left( 4{{e}^{2}}-7 \right)=4{{e}^{2}}\times \left( {{e}^{2}}-1 \right)\].
\[\Rightarrow 20{{e}^{2}}-35=4{{e}^{4}}-4{{e}^{2}}\].
\[\Rightarrow 4{{e}^{4}}-4{{e}^{2}}-20{{e}^{2}}+35=0\].
\[\Rightarrow 4{{e}^{4}}-24{{e}^{2}}+35=0\].
We have found the condition for eccentricity of hyperbola as \[4{{e}^{4}}-24{{e}^{2}}+35=0\].
∴ The condition for eccentricity of hyperbola is \[4{{e}^{4}}-24{{e}^{2}}+35=0\].
So, the correct answer is “Option A”.
Note: We can also solve the problem by finding the value of eccentricity using the value of $\dfrac{a}{e}$ and substituting it in the options to verify which is the correct option. We need to make sure about the center of the given hyperbola. If the center changes, then the total answer changes with a lot of deviation from the answer we just had. Similarly, we expect to find the values of a, b and also the equation of the axes, foci of the given hyperbola.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE